Competitive tasks in trigonometry: problematic aspect - Narkevičienė, Bronė; Papreckienė, Laima (Lietuvos matematikos rinkinys, 2003)
The article presents the results of analysis of solutions of trigonometrical tasks in KTU J. Matulionis contest of young mathematicians. The study showed that the problems of integration of knowledge and skills as well as understanding of the definition of exponent function and the answer of trigonometrical equation are still important in teaching of mathematics.